The Bonsai as an alternative safety duplication system of the world cassava collection preserved at CIAT - Niño, Diana Patricia; Aranzales Rondón, Ericson; Erazo, Juan Camilo; López, Jhon Jenry; Vélez, Mónica (International Center for Tropical Agriculture, 2016)
The germplasm bank of CIAT houses more than 6,000 accessions of cassava (Manihot esculenta Crantz) constituting the most important collection for this crop. In order to guarantee the safety of the materials, the collection has an international duplicate kept at the International Potato Center (CIP) in Peru under in vitro conditions. However, due to the difficulties in having this system of duplication sustained for long periods of time, it was decided to keep the backup on a slow-growth scheme under greenhouse conditions. In vitro plants must undergo a hardening or acclimatization phase of approximately four weeks, which takes into account factors such as substrate, control of environmental conditions and pathogens to prevent loss of material. In this work, the use of a methodology for the establishment of materials in greenhouse was evaluated and compared with four systems previously used for this purpose. Modification in the substrate, the use of a biological inoculant, moist chamber conditions and fertilization allowed the establishment of 1,818 accessions with a loss rate of less than 4%, compared to the initial number of plants (1,886) which indicates that the methodology evaluated is adequate for their hardening. The plants were obtained from the in vitro cassava collection and were tested and found free from three diseases considered of quarantine for the Americas: Cassava common mosaic virus, Cassava frogskin agent and Cassava virus “X”. These materials have also been tested and found to be free of Reovirus, Luteovirus, Torradovirus and Potexvirus. The bonsai copy allows to safeguard a greater percentage of accessions for prolonged periods, since, by restricting the growth of the root in plastic containers and with controlled prunings, it is possible to maintain the plants for more than two years, time greater than achieved with the duplication systemwith in vitro techniques.